Inclusion and differentiation: an examination of teachers' experience and perspectives in working with difference and learner potential in grade 1 mathematics classrooms in three schools in Grahamstown - Whittington-Jones, Alexandra (Rhodes University, Faculty of Education, Department of Education, 2013)
In South Africa, in July 2001, the National Department of Education released White Paper 6 which underpins the notion of inclusive education. It states that the needs of all children should be catered for within the South African educational framework. Subsequent guidelines from the Department (2005; 2012) also provide a strong focus on understanding individual children's learning styles and explain the concept and application of children's multiple intelligences. However, on closer examination, it seems that the inclusive education, as well as barriers to learning referred to in the abovementioned guidelines, are indicated to mean catering for children at the lower-ability end of the learning spectrum. This research begins to explore the notion that high potential children might require special attention, though not at the expense of those with learning impairments. An education system that provides inclusive education to children at both the lower and higher ends of the learning spectrum would be more equitable, and would give all children an equal chance of reaching their full potential. One possible strategy for accommodating the diverse needs of learners is through differentiation (Department of Education, 2005). Differentiation is a way of teaching that aims to provide stimulating and enriching learning environments to a diverse group of children within a classroom. This might be achieved by separating the class into smaller groups based on ability, or by providing children with different tasks at the same time, with the same learning objectives but at differing cognitive levels (Rogers, 2007). Vygotsky's work on the Zone of Proximal Development (ZPD) and mediation provides a theoretical framework for proposing differentiation as a strategy. The data was gathered through an in-depth examination (using a combination of classroom observations, document analysis and teacher interviews) of mathematics teaching in Grade 1 in three schools in Grahamstown. My analysis was based on Vygotsky's theories (the main tenets of which were the ZPD and scaffolding, as well as the role of socio-culture in learning), using Tomlinson's (1999) differentiated instruction framework to provide structure to the study. The following themes emerged from the data: a focus on the teachers' understandings of differentiation; the use of grouping as a superficial form of differentiation; a lack of teacher preparation and understanding in relation to task differentiation; and an underlying sense of 'sameness' in teachers' understanding of their learners. In addition to the above, I did not observe evidence of real differentiation for high potential children and hope that this research contributes to extending teachers' training (both academic and in-service) in this area, convincing teachers of the existence and importance of critical thinking abilities in our youngest learners, and initiating a move towards the drafting of Individual Education Plans for all our learners. During the period of my research I have been convinced that the use of differentiated instruction in classrooms is the way forward in educational thinking, particularly as it relates to the notion of inclusive learning. Clearly there are challenges to be addressed in terms of school timetables, curricula, teachers' time frames and past education system inequalities such as we have here in South Africa.
Keywords: Gifted children -- Education (Primary) -- Research -- South Africa -- Grahamstown; Inclusive education -- Research -- South Africa -- Grahamstown; Mainstreaming in education -- Research -- South Africa -- Grahamstown; Special education -- Research -- South Africa -- Grahamstown; Curriculum planning -- Education (Primary) -- South Africa -- Grahamstown; Education, Primary -- Study and teaching -- South Africa